Prognostic significance of FT3 levels in hypertrophic cardiomyopathy patients with HFpEF - Yang, Zhen-Yu; Zhang, Zhi-Yuan; Zhang, Wei-Jie; Liu, Da; Piao, Fu-Shi; Yan, Xiangyu; Shi, Fang-Tao; Yang, Min; Chen, Jing; Zhu, Sheng-song; He, Hong-Hou; Wu, Pei-Hong; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study sought to identify key prognostic factors in patients with hypertrophic cardiomyopathy (HCM) and heart failure with preserved ejection fraction (HFpEF), emphasizing the prognostic role of free triiodothyronine (FT3) levels.Research design and methodsThis retrospective cohort study enrolled 992 HCM-HFpEF patients from two Chinese medical centers between 2009 and 2019, excluding those with thyroid-affecting medications or disorders. Data on demographic and clinical variables, including FT3, were analyzed using univariate and multivariate Cox regression, Kaplan–Meier (KM) survival analysis, and restricted cubic spline (RCS) analysis to explore prognostic factors and FT3's nonlinear predictive value.ResultsAge, atrial fibrillation, and NT-proBNP levels significantly influenced prognosis, while FT3 emerged as an independent predictor of all-cause mortality and cardiac transplantation (P < 0.001). Patients with lower FT3 exhibited poorer long-term outcomes, with RCS identifying a critical threshold of 2.885 pg/ml (P-non-linear < 0.05).ConclusionsFT3 is a robust prognostic marker in HCM-HFpEF patients, supporting its integration into risk stratification. Clinicians should monitor FT3 levels, though intervention efficacy requires further prospective validation.